2014
DOI: 10.1016/j.biomaterials.2013.09.091
|View full text |Cite
|
Sign up to set email alerts
|

Avidin as a model for charge driven transport into cartilage and drug delivery for treating early stage post-traumatic osteoarthritis

Abstract: Local drug delivery into cartilage remains a challenge due to its dense extracellular matrix of negatively charged proteoglycans enmeshed within a collagen fibril network. The high negative fixed charge density of cartilage offers the unique opportunity to utilize electrostatic interactions to augment transport, binding and retention of drug carriers. With the goal of developing particle-based drug delivery mechanisms for treating post-traumatic osteoarthritis, our objectives were, first, to determine the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
232
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(249 citation statements)
references
References 49 publications
(57 reference statements)
14
232
2
1
Order By: Relevance
“…In a previously published in vitro study using 1 mm thick young bovine cartilage explants, we reported >90% retention of Avidin for at least 15 days. 22 In vivo, a decrease in retention time is expected (compared to in vitro explants) due to the presence of convective transport and clearance by the lymphatic system. By day 7 in the rat model, Avidin retention was only 4.1% of the initial value at 24 h after i.a.…”
Section: Discussionmentioning
confidence: 99%
“…In a previously published in vitro study using 1 mm thick young bovine cartilage explants, we reported >90% retention of Avidin for at least 15 days. 22 In vivo, a decrease in retention time is expected (compared to in vitro explants) due to the presence of convective transport and clearance by the lymphatic system. By day 7 in the rat model, Avidin retention was only 4.1% of the initial value at 24 h after i.a.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in density causes a reduction in pore size which results in the inability of many large solutes to penetrate through the depth of cartilage [22]. Penetration of solutes throughout the full thickness of tissue allows for longer retention times and as a result, longer therapeutic times.…”
Section: Articular Cartilagementioning
confidence: 99%
“…Penetration of solutes throughout the full thickness of tissue allows for longer retention times and as a result, longer therapeutic times. In a study conducted by Bajpayee et al, results showed that solutes having a hydrodynamic diameter of 10 nm or less were able to penetrate through the full thickness of cartilage, whereas larger sized solutes became trapped within the superficial zone of cartilage [22]. This implies that the use of either liposomes or microparticles as delivery mechanisms for cartilage therapy are not realistic approaches.…”
Section: Articular Cartilagementioning
confidence: 99%
See 2 more Smart Citations